2023
DOI: 10.1088/1742-6596/2507/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

On a road map for technology qualification, innovation and cost reduction in floating offshore wind: learning from Hywind and Norwegian approach

Abstract: The main aim of this paper is to synthetize and to learn from the existing road maps and the Norwegian approach on the floating offshore wind. It targets to identify main priorities, key challenges, and technological qualification for the floating offshore wind development. The Norwegian approach is evaluated in the view of the key success factors of the offshore wind market highlighted by the World Bank. One particularity of the national Norwegian offshore landscape is the usage of the Norwegian floating wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The literature on dynamic power cables for the oil and gas sector shows several examples of offshore applications, but the main starting point for this study is the documentation provided by the EU project Corewind on floating offshore wind [10]. One challenge with floating offshore wind is often that the power rating of dynamic power cable examples from floating offshore demonstrations are in the range of a few MW, such as Hywind [11], Stiesdal [12] and Principle Power [13], and will have to be scaled to power levels above 15-20 MW expected for the future offshore wind farms. A conceptual dynamic reference power cable can be used for such simple upscaling to describe the expected layout of future dynamic power cables for floating offshore.…”
Section: Reference Dynamic Power Cable For Wind Farm Of 15 Mw Referen...mentioning
confidence: 99%
“…The literature on dynamic power cables for the oil and gas sector shows several examples of offshore applications, but the main starting point for this study is the documentation provided by the EU project Corewind on floating offshore wind [10]. One challenge with floating offshore wind is often that the power rating of dynamic power cable examples from floating offshore demonstrations are in the range of a few MW, such as Hywind [11], Stiesdal [12] and Principle Power [13], and will have to be scaled to power levels above 15-20 MW expected for the future offshore wind farms. A conceptual dynamic reference power cable can be used for such simple upscaling to describe the expected layout of future dynamic power cables for floating offshore.…”
Section: Reference Dynamic Power Cable For Wind Farm Of 15 Mw Referen...mentioning
confidence: 99%
“…Research by Mathern et al (2020) revealed that in 2019, fixed offshore wind farms globally comprised 4258 monopile structures, 301 gravity-based foundations, 468 jacket structures, 126 tripod structures, and 80 tripile structures [27]. By the end of 2023, four floating wind farms were operational worldwide, boasting individual capacities surpassing 24 MW: Hywind Scotland (UK) (30 MW), Kincardine (UK) (50 MW), Windfloat Atlantic (Portugal) (25 MW), and Hywind Tampen (Norway) (88 MW) [12,28,29]. The cumulative installed capacity of floating wind farms globally reached 211.4 MW by the end of 2023 [12,29,30].…”
Section: Literature Review Of Recent Researchmentioning
confidence: 99%
“…By the end of 2023, four floating wind farms were operational worldwide, boasting individual capacities surpassing 24 MW: Hywind Scotland (UK) (30 MW), Kincardine (UK) (50 MW), Windfloat Atlantic (Portugal) (25 MW), and Hywind Tampen (Norway) (88 MW) [12,28,29]. The cumulative installed capacity of floating wind farms globally reached 211.4 MW by the end of 2023 [12,29,30]. Various types of supporting floating structures, including semi-submersible, tension leg platform (TLP), and spar, have been developed [31].…”
Section: Literature Review Of Recent Researchmentioning
confidence: 99%
“…Recent advancements in robotics have transformed maintenance practices in the offshore oil and gas industry. Innovations in robotic technology have enabled the development of specialized robots capable of performing a wide range of maintenance tasks with precision and efficiency (Ibrion and Nejad, 2023).…”
Section: Advancements In Robotics For Maintenance Tasksmentioning
confidence: 99%